2021
DOI: 10.1002/ajs4.196
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study examining the changes to Australia’s social security system during COVID‐19 lockdown measures

Abstract: During the 2020 COVID‐19 wave, the Australian Government made an additional $550 Coronavirus Supplement available for people receiving social security payments, and temporarily suspended mutual obligation requirements. By doing so, the government effectively gave people who had been long stigmatised and subject to punitive conditionality to compel them into the labour market, financial security and their time back. Drawing on survey responses from people who received the $550 Supplement and had their mutual ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Morrison also said that: ‘What we have to be worried about now is that we can't allow the JobSeeker Payment to become an impediment to people going out and doing work, getting extra shifts’. Government Members of Parliament travelling to regional areas cited anecdotes in the media as to how the additional cash in remote First Nations communities was causing increased drug and alcohol use ( Marchant & Pedler, 2020 ) – a narrative long deployed to discredit First Nations people, and to justify punitive programs targeting them ( Bielefeld, 2018 ).…”
Section: Not Permanent and Not Universalmentioning
confidence: 99%
“…Morrison also said that: ‘What we have to be worried about now is that we can't allow the JobSeeker Payment to become an impediment to people going out and doing work, getting extra shifts’. Government Members of Parliament travelling to regional areas cited anecdotes in the media as to how the additional cash in remote First Nations communities was causing increased drug and alcohol use ( Marchant & Pedler, 2020 ) – a narrative long deployed to discredit First Nations people, and to justify punitive programs targeting them ( Bielefeld, 2018 ).…”
Section: Not Permanent and Not Universalmentioning
confidence: 99%
“…Additionally, researchers undertook an online survey of 146 social security clients in Australia to determine how people were spending the Supplement, how they were using their time, and what the impact was on their subjective wellbeing (Klein et al , 2021: 6). The key findings from this study included that both the Supplement and the suspension of mutual obligations improved respondents’ physical and mental health.…”
Section: Governing Unemployment Through a Public Health Crisismentioning
confidence: 99%
“…To address the problem as represented, strict levels of conditionality characterise social security in Australia. The resulting ‘hostile conditions’ have been well‐documented and criticised as a conscious policy decision to deter individuals and families from seeking support (Brady, 2011 ; Klein et al, 2021 ; Mills & Klein, 2021 ). Parenting support is means‐tested by both assets and income, and is only available to partnered parents until a child turns 6 years of age and to single parents until the youngest child turns eight.…”
Section: Covid ‐19 Responses and Materials Deprivationmentioning
confidence: 99%
“…In 2020, the Australia Institute reported that 65,000 children from birth to 14 years had been lifted out of poverty due to the Coronavirus Supplement (Grundoff, 2020 ); other estimates put the number of children affected far higher (Anti‐Poverty Week, 2021 ). A survey (Klein et al, 2021 ) of how people used the additional income provided by the Supplement, and the additional time gained by not having to fulfil mutual obligations, found it was used for essential items, such as food, medicine and housing, and improved health, well‐being and ability to participate in a range of activities. Respondents reported being able to better provide for their children (Klein et al, 2021 ).…”
Section: Covid ‐19 Responses and Materials Deprivationmentioning
confidence: 99%
See 1 more Smart Citation